The AI metaverse revolution. volume 2 : transforming multi-business scenarios - Kumar, Jeetesh; Arora, Manpreet (Emerald Publishing Limited, 2025)
The AI Metaverse Revolution: Transforming Multi-Business Scenarios (Volume 2) explores the profound convergence of Artificial Intelligence (AI) and the Metaverse, and its transformative effects on business decision-making and strategy. As these technologies evolve, they offer businesses unprecedented tools for operating more efficiently, engaging customers in innovative ways, and responding to rapidly shifting market dynamics. By examining the role of AI in analysing vast data sets and the insights gained from virtual environments within the Metaverse, this volume provides a comprehensive guide to harnessing these cutting-edge technologies for competitive advantage. Through in-depth analysis and real-world examples, the diverse range of global contributors explore how AI and the Metaverse are driving a new era of business possibilities across industries. From AI-powered data analysis that enables businesses to make informed, real-time decisions; to personalised customer experiences created through behavioural analysis in virtual spaces, this volume presents actionable strategies for integrating AI and the Metaverse into modern business practices. It offers readers a roadmap for navigating this technological revolution, positioning AI and the Metaverse as essential components of future-proof business strategy.